Case Report: Recurrent pediatric cavernous malformation of the trigeminal nerve - Harty, Mikhail; Baqai, Muhammad Waqas Saeed; Sajjad, Jahangir; Fellows, Greg; Clamp, Philip J.; Abhinav, Kumar (Frontiers in Surgery, 2023)
Most cavernous malformations (CM) usually involve the parenchyma and rarely occur in cranial nerves. 1 Recurrence of CM associated with cranial nerves after surgical resection has not been previously reported.This paper describes the case of an 11-year-old girl who presented with left otalgia and headache because of a left trigeminal cavernous malformation. She underwent radical resection via a left retrosigmoid approach while sparing the trigeminal nerve. Surveillance imaging at 18 months demonstrated recurrence along the length of the trigeminal nerve into Meckel's cave with significant extension into the middle cerebellar peduncle. Subsequent re-operation via an extended middle fossa approach with anterior petrosectomy enabled complete resection with division of the trigeminal nerve. Postoperatively, she had a transient left facial paresis, and right hemiparesis that resolved within 48 hours.This case highlights the importance of close postoperative surveillance in CM associated with cranial nerves as recurrence after nerve-sparing resection is possible. Surgical treatment due to the morphology of significant recurrence required the use of a complex skull base approach through a new corridor to achieve optimal clinical outcome.